Effect of β-alanine on the athletic performance and blood amino acid metabolism of speed-racing Yili horses - Li, Xiaobin; Ma, Jun; Li, Haiying; Li, Hai; Ma, Yuhui; Deng, Haifeng; Yang, Kailun (Frontiers in Veterinary Science, 2024)
The objective of this study was to examine the effects of supplemental β-alanine feeding on the athletic performance of Yili horses involved in speed racing, focusing on alterations in plasma free amino acid patterns pre and post exercise. Additionally, the research aimed to evaluate the effects of carnosine on the plasma acid–base buffering capacity and antioxidant levels in these horses. Twelve Yili horse stallions, averaging 3 years in age and 346.50 ± 21.39 kg in weight, were chosen and randomly divided into two groups: a control group and a test group, each comprising six horses. The control group received a supplementation of 300 mg/kg BW/day of α-alanine, while the test group received 300 mg/kg BW/day of β-alanine. This supplementation regimen was maintained for a 30-day supplementation trial period, under identical feeding and management conditions. Throughout the trial, the horses participated in the 1,000 Speed Race, and three distinct blood samples were gathered for assessing plasma free amino acids, blood gases, biochemical parameters, and antioxidant parameters. The outcomes indicated a considerable enhancement in the 1,000 m exercise performance of the speed racing Yili horses in the test group compared to the control group, showcasing a noteworthy improvement of 12.01%, with the test group completing the race 13.29 s faster. Notably, the α-alanine content in the plasma of the control group Yili horses remained higher than that of the test group, demonstrating a consistent increasing trend. By contrast, the plasma β-alanine content was notably higher in the test group than in the control group. Over the course of the supplementation period, plasma β-alanine exhibited an escalating and then stabilizing trend in the test group, whereas in the control group, although β-alanine content also increased, the trend was less pronounced. The plasma levels of histidine and carnosine showed minimal variance between the two groups. Overall, the test group of Yili horses exhibited slightly higher plasma levels of histidine and carnosine compared to the control group. The addition of β-alanine to their diet for a duration of 30 days notably affected the plasma levels of amino acids both pre- and post-exercise in speed-racing Yili horses. Furthermore, β-alanine demonstrated an inhibitory effect on the catabolism of these horses’ bodies during high-intensity exercise. Ten marker amino acids, including valine, leucine, β-alanine, isoleucine, carnosine, 3-methyl-histidine, lysine, ethanolamine, argnine, and taurine, displayed statistically significant changes. β-alanine notably increased the blood glucose levels of Yili horses and played a role in expediting the restoration of blood gas levels post-exercise. Moreover, in the test group of Yili horses, the levels of superoxide dismutase, glutathione peroxidase, and total antioxidant capacity significantly increased both before and after the race, while the content of malondialdehyde, an oxidation product, exhibited an extremely significant decrease immediately after the race. These outcomes suggest that the addition of β-alanine significantly augmented antioxidant levels during high-intensity exercise in Yili horses. Consequently, it reduced post-exercise injuries and accelerated the recovery process after exercise.